2013
DOI: 10.1088/0031-9155/58/18/6429
|View full text |Cite
|
Sign up to set email alerts
|

Image quality improvements of electronic portal imaging devices by multi-level gain calibration and temperature correction

Abstract: Amorphous silicon (aSi:H) flat panel detectors are prevalent in radiotherapy for megavoltage imaging tasks. Any clinical and dosimetrical application requires a well-defined dose response of the system to achieve meaningful results. Due to radiation damages, panels deteriorate and the linearity of pixel response to dose as well as the stability with regard to changing operating temperatures get worse with time. Using a single level gain correction can lead to an error of about 23% when irradiating a flood fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Huber et al reported noticeable image quality improvements with the MLG calibration over the SLG calibration. 10 We also observed better image quality after the MLG calibration, especially the reduction of shadow banding artifacts. With the Las Vegas phantom, it led to the conclusion that both calibration methods were satisfactory.…”
Section: Metricsupporting
confidence: 51%
See 3 more Smart Citations
“…Huber et al reported noticeable image quality improvements with the MLG calibration over the SLG calibration. 10 We also observed better image quality after the MLG calibration, especially the reduction of shadow banding artifacts. With the Las Vegas phantom, it led to the conclusion that both calibration methods were satisfactory.…”
Section: Metricsupporting
confidence: 51%
“…In reality, however, the actual response, particularly at low-dose region, is nonlinear due to poorer pixel sensitivity and its characteristics may have changed since the last calibration as the panel ages. 10 The SLG calibration usually works well for a relatively new panel; however, it may lead to poor image quality in the lowdose region as the panel ages (Fig. 4).…”
Section: Metricmentioning
confidence: 99%
See 2 more Smart Citations
“…The two sections are read synchronously, column by column, from the outside to the inside of the panel. 19,20 Therefore, for the section on the linac A-side, the readout starts at column c ¼ 0 at t ¼ 0 and ends at col-…”
Section: B | Acquisition Modulesmentioning
confidence: 99%